Cefoxitin Prophylaxis During Pediatric Cardiac Surgery: Retrospective Exploration of Postoperative Trough Levels. Issue 5 (May 2019) - Ricci, Zaccaria; Benegni, Simona; Cies, Jeffrey J.; Marinari, Eleonora; Haiberger, Roberta; Garisto, Cristiana; Cairoli, Sara; Di Chiara, Luca; Goffredo, Bianca
Abstract : Background: This study aimed to explore inter-individual variability of cefoxitin trough levels, predictors of serum cefoxitin concentration and the probability of target attainment of drug levels above 4 mg/L after pediatric cardiac surgery. Methods: Retrospective study on children scheduled for elective cardiac surgery and having cefoxitin trough levels available up to 24 hours postsurgery. Results: Overall, 68 children (9 neonates, 34 infants, 15 children below or equal to 10 years old and 10 patients above this age) were included. Of these, 16 surgeries were performed off cardiopulmonary bypass and 52 were performed on cardiopulmonary bypass. The free cefoxitin concentrations showed a median (interquartile range) concentration of 1.7 (0.6–4.2) mg/L. The range of cefoxitin concentrations showed a 150-fold and 340-fold variability at cardiac intensive care unit admission and after 24 hours, respectively. The pharmacodynamics (PD) targets of free cefoxitin at 100% of the dosing interval, considering Eucast breakpoints for Methicillin Sensitive Staphylococcus Aureus (4 mg/L) and E.Coli (8 mg/L), were obtained in 28% and 16% of patients, respectively. Patient weight (odds ratio, 0.7; 95% confidence interval, 0.62–0.92; P = 0.006) and serum creatinine concentrations (odds ratio, 25; 95% confidence interval, 18–36; P = 0.004) showed a significant relationship with the PD targets. Conclusions: Cefoxitin trough concentrations vary significantly in the first 24 hours after pediatric cardiac surgery. Both serum creatinine and body weight showed independent associations with cefoxitin concentration. The PD target was not obtained in the vast majority of the explored population, regardless of the target bacteria.